An examination of direct, indirect and reciprocal relationships between perfectionism, eating disorder symptoms, anxiety, and depression in children and adolescents with eating disorders - Drieberg, H.; McEvoy, Peter; Hoiles, K.; Shu, C.; Egan, S. (Pergamon, 2019)
Objective: Perfectionism is a transdiagnostic factor across eating disorders, anxiety, and depression. Previous research has shown anxiety mediates the relationship between perfectionism and eating disorders in adults. The aim of this study was to investigate the relationships between anxiety/depression, perfectionism and eating disorder symptoms in children and adolescents with eating disorders. Method: Structural equation modeling was used to investigate three models in a clinical sample of children and adolescents (N = 231, M age = 14.5, 100% female): (1) anxiety and depression as mediators of the relationship between perfectionism and eating disorder symptoms, (2) eating disorder symptoms as a mediator of the relationship between perfectionism and anxiety and/or depression, and (3) perfectionism as a mediator of the relationship between anxiety/depression and eating disorders. Results: Results indicated that both models 1 and 2 fit the data well, while model 3 provided a poor fit. These findings suggest that in clinical populations of children and adolescents, anxiety and depression mediate the relationship between perfectionism and eating disorder symptoms, and there is also a reciprocal relationship whereby eating disorders mediate the association between perfectionism, and anxiety and/or depression. Discussion: The results highlight the importance of further research to determine whether targeting perfectionism is helpful in the treatment of eating disorders and comorbid anxiety and depression in young people. It would be useful for clinicians to consider assessing for and treating perfectionism directly when it is elevated in children and adolescents with eating disorders.